Emotion: Woman's Strength or Frailty? (KEMANUSIAAN The Asian Journal of Humanities, 2010)
Edith Stein's viewpoint on woman presents a fuller sense of the metaphysical notion of the being of woman. Stein's position is that woman?s nature as biological mother affects her whole being. Woman has two essential characteristics: attraction to the personal and attraction to wholeness. It is woman's emotions that account for these distinctly feminine traits. Woman is distinguished by her empathetic perception of persons, an intuitive grasp of a person's being and value as "person". Stein describes empathy as a clear awareness of another person, not simply of the content of his/her experience, but of his/her experience of that content. In empathy, one takes the place of the other without becoming strictly identical to him/her. One does not simply understand the experiences of the other, but takes them on as one's own. Stein reinterprets traditional readings of woman, challenging claims of the woman as the "weaker sex" and of emotions as inferior to reason.